1999
DOI: 10.1046/j.1523-536x.1999.00083.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Labor Analgesia on Breastfeeding Success

Abstract: In a hospital that strongly promotes breastfeeding, epidural labor analgesia with local anesthetics and opioids does not impede breastfeeding success. We recommend that hospitals that find decreased lactation success in parturients receiving epidural analgesia reexamine their postdelivery care policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 26 publications
0
61
1
1
Order By: Relevance
“…Similarly, the study of 171 women by Halpern et al 15 showed no early or late (6 to 8 weeks' postpartum) adverse effects on breast-feeding by the use of epidural anesthesia during labor. Women having cesarean sections were included and not segregated in either study.…”
mentioning
confidence: 86%
“…Similarly, the study of 171 women by Halpern et al 15 showed no early or late (6 to 8 weeks' postpartum) adverse effects on breast-feeding by the use of epidural anesthesia during labor. Women having cesarean sections were included and not segregated in either study.…”
mentioning
confidence: 86%
“…Lactational amenorrhea decreases iron loss. Lactation reduces the risk of postpartum hemorrhage, makes it easier to return to pre-pregnancy weight, increases bone remineralization, reduces the possibility of osteoporosis and reduces the risks of developing breast, ovarian and uterine cancers premenopausally [15,[26][27][28][29].…”
Section: Breastfeedingmentioning
confidence: 99%
“…Halpern et al [26] prospectively enrolled 189 women who delivered at a hospital. A total of 59% of the women received epidural analgesia.…”
Section: Neuraxial Analgesia During Labormentioning
confidence: 99%
“…Observational studies concerning EDA are, however, subject to selection bias. Moreover, there are studies with no difference in breastfeeding performance (Halpern et al 1999). In a systematic review, Leighton and Halpern (2002) concluded that EDA does not affect breast-feeding initiation or management.…”
Section: Effects Of Maternal Analgesia On the Neonatementioning
confidence: 99%